CONDITION OF THE ONCOLOGICAL HELP TO THE PATIENT WITH CANCER OF A BLADDER IN KRASNODAR REGION - M. G. Leonov; M. V. Kazantseva; A. A. Tkhagapso; O. I. Agrarova (Кубанский научный медицинский вестник)
The dynamic analysis of quality indicators of rendering the special help to the patients with cancer of a bladder (morphological verification, phasic diagnostics, neglect, one-year lethality, preventive detectability and others) in Krasnodar region for the period 2003-2012 is presented in article. Treatment results of 572 patients with cancer of a bladder within 10 years are given here.